[Hikers at Landmannalaugar] - Streng, Evelyn Fiedler (1975)
Photograph of hikers at Landmannalaugar. The tall grey, rocky mountains surround a white river cutting through it in the bottom left corner of the photograph. Loose rocks surround the water and climb up the hill to the right. Two hikers in orange and yellow rain ponchos walk along the rocky mountainside at the bottom of the photograph.